The influence of brand equity towards purchase intention of Agromas product / Mohamad Azali Abdullah - Abdullah, Mohamad Azali (Faculty of Business and Management, 2018)
High brand equity is very important to companies in order to compete in the global market today. This paper examines the relationship between brand equity and customer purchase intention in relation to Agromas products. Brand equity elements consists of brand awareness, brand loyalty, perceived quality and brand association. The questionnaire was distributed to 100 consumers of Agromas in Kuala Pilah. Convenience sampling was used in this research and data were analyzed using SPSS version 22. The results of the study indicates that there are significant positive relationship between brand equity and purchase intention of Agromas products. The results also shows that brand loyalty has the strongest impact on purchase intention.